Uso de aditivo fitogênico em sistema de produção sem o uso de ractopamina para suínos - Domingos, Rodrigo de Lima (2019)
The objective of this study was to compare the effects of ractopamine and a commercial phytogenic additive on the performance and carcass characteristics, as well as the microbiological and morphometric characteristics of finishing pigs. Sixty female pigs with an approximate age of 70 days and initial weight of 32.0 kg ± 2.6 kg were distributed in a randomized complete block design with three treatments and ten replicates of two animals per pen. The treatments consisted of a control diet (T1), a diet of 15 ppm of ractopamine supplied in the 21 days before to slaughter (T2) and a diet with 100 g / ton of commercial phytogenic additive based on carvacrol, thymol and cinemaldehyde supplied throughout the experimental period, which was 100 days. RAC increased (P<0.02) the final weight and weight gain of the animals, reduced (P<0.01) the feed conversion ratio and provided higher (P<0.05) weights of hot and cold carcass and larger area of loin eye. Compared to the control, the phytogenic additive did not influence the performance and carcass characteristics of the animals (P>0.05). There were no differences (P>0.05) in the microbiological and morphological characteristics of the jejunum nor in the incidence of diarrhea in the animals. It is concluded that the RAC is able to improve performance and carcass traits of pigs in termination in a superior way to the phytogenic additives, without influencing the microbiota and morphometry of intestinal mucosa. The commercial phytogenic additive used did not confer any production benefit in growing and finishing phase.